Treatment of unstable distal radius fractures with the volar locking plate - Minegishi, Hanae (Informa Healthcare, 2011)
BACKGROUND: Open reduction and internal fixation using an interlocking plate system has gained popularity for the treatment of dorsally displaced distal radius fractures. PURPOSE: To evaluate the functional and radiological results of treating unstable distal radius fractures with the volar locking plate. PATIENTS AND METHODS: A retrospective review was conducted of patients from one institution using the volar locking plate to treat intra-articular and extra-articular distal radius fractures. Unstable distal radius fractures in 15 patients, comprising 3 men and 12 women with a mean age of 64.4 years (34–76 years), were treated with a volar locking compression plate (Acu-Loc distal radius plate system; Acumed, Oregon, USA) and followed up for a minimum of 1 year. Fractures were classified using the AO classification. Radiographic parameters of preoperative, postoperative, and final follow-up radiographs were compared. The time to initiation of active range of motion was determined. Final follow-up range of motion and complications were reported. RESULTS: At final functional assessment, the scores of 5 patients were excellent, 7 patients good, and 3 patients fair according to Cooney's Clinical Scoring Chart. No non-union or infection occurred. Rupture of the flexor pollicis longus tendon occurred in 1 patient. CONCLUSION: Treatment of unstable distal radius fractures with a volar locking plate leads to satisfactory results, provided the operative technique is carefully performed to prevent complications.